1996
DOI: 10.1016/0014-5793(96)00646-1
|View full text |Cite
|
Sign up to set email alerts
|

Thimerosal modulates the agonist‐specific cytosolic Ca2+ oscillatory patterns in single pancreatic acinar cells of mouse

Abstract: Modulation of the agonist-specific cytosolic Ca 2+ o~cillatory pattern by thimerosal has been investigated in single pancreatic acinar cells using patch-clamp perforated whole-cell recording to measure the calcium-dependent chloride current (lcl(c~÷)). 1 gM thimerosal, which falls to evoke Ca 2+ oscillation alone, clearly changed the pattern of Ca 2+ oscillation from pulsatile spikes (evoked by low concentrations of activators) to sinusoidal or transient oscillations. The mimetic action of thimerosal was indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…Regarding the main channels for calcium release from internal stores, thiol oxidants acting on sulfydryl residues release calcium through IP 3 R (5, 7, 52) and RyR (1,23,80), a mechanism that enhances (and even elicits) Ca 2ϩ oscillations in exocrine cells (81,90) and HeLa cells (5). This process could be due to sensitization of IP 3 R-mediated calcium release (51,52) to resting IP 3 levels, a phenomenon that has been integrated in a model to facilitate calcium oscillations (52).…”
Section: Mitochondrial Production Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Regarding the main channels for calcium release from internal stores, thiol oxidants acting on sulfydryl residues release calcium through IP 3 R (5, 7, 52) and RyR (1,23,80), a mechanism that enhances (and even elicits) Ca 2ϩ oscillations in exocrine cells (81,90) and HeLa cells (5). This process could be due to sensitization of IP 3 R-mediated calcium release (51,52) to resting IP 3 levels, a phenomenon that has been integrated in a model to facilitate calcium oscillations (52).…”
Section: Mitochondrial Production Of Reactive Oxygen Speciesmentioning
confidence: 99%
“…Patch-clamp, whole-cell recording Ca 2+ -activated Cl -currents were recorded using conventional whole-cell recordings to monitor intracellular Ca 2+ signal oscillations as previously reported [17][18][19] . When the recording pipette was filled with the K + -containing pipette solution, the resistance was 3-4 MΩ.…”
Section: Methodsmentioning
confidence: 99%
“…Acutely dissociated mouse pancreatic acinar cells Single pancreatic acinar cells were dissociated as previously described [17][18][19] . Briefly, adult (4-6 months old) male CD1 mice were anesthetized with isoflurane, and then the pancreas was rapidly removed and injected with collagenase (200 U/mL) dissolved in standard extracellular solution(see below).…”
Section: Methodsmentioning
confidence: 99%
“…In fact, it has been reported that other oxidising agents, like H 2 O 2 , release Ca 2+ from intracellular stores by activation of the ryanodine receptor (Favero et al, 1995;Oba et al, 1998) and that sulphydryl groups (susceptible to oxidation) have a critical role in the ryanodine-sensitive Ca 2+ channel (Oba et al, 1998). In addition, ryanodine shows 'in vitro' sensitisation in the presence of the sulphydryl group oxidising agent thimerosal (Abramson et al, 1995;Wu et al, 1996).…”
Section: Inmentioning
confidence: 99%